Tinjauan Yuridis Integrasi Nilai-Nilai Hukum Konstitusi dan Adat Minangkabau Dalam Penyusunan Peraturan Daerah Di Sumatera Barat - Parlindungan S, Gokma Toni; Agustini, Sri; Arika, Andri; Ramadayanti, Sari (Universitas Sumatera Barat, 2023)
In the context of local governance in Indonesia, the harmonization of national law and customary law presents a significant challenge. This study examines the juridical integration of constitutional values with Minangkabau adat in the formulation of regional regulations (Perda) in West Sumatra. The study is based on the premise that regional regulations must align with constitutional principles, while West Sumatra also has a strong and influential customary law heritage in its community life. Using a normative juridical approach, this research aims to analyze how constitutional values can be harmonized with Minangkabau customary norms in the regional legislative process, as well as identify the legal challenges that arise in this endeavor. The findings reveal that although there is potential tension between constitutional law and customary law, with the right approach, these two legal systems can be synergized to produce Perda that are constitutionally valid while maintaining social legitimacy and relevance in the local community. The study also provides strategic recommendations for the formulation of Perda in West Sumatra that considers the harmonization between national law and local wisdom.